Air pollution (PM2.5) and its meteorology predictors in Kampala and Jinja cities, in Uganda - Alaran, Aishat Jumoke; O'Sullivan, Natasha; Tatah, Lambed; Sserunjogi, Richard; Okello, Gabriel (Royal society of chemistry, 2024)
Air pollution disproportionately affects African countries, including Uganda, but it is inadequately studied in these settings. The emergence of low-cost sensors offers an opportunity to improve routine air quality monitoring, assess interventions, and track progress. This study aimed to assess the spatiotemporal trends of PM 2.5 in Kampala and Jinja cities in Uganda, whilst exploring the influence of meteorological parameters on PM 2.5 . Calibrated PM 2.5 values and meteorological parameters for three years (2020 to 2022) were obtained from 58 local low-cost sensors and 6 weather stations. Hourly averages for PM 2.5 and meteorological data underwent necessary pre-processing, and various statistical analyses, including descriptive statistics, time series trends, spatial variation, Spearman rank correlation, and multivariate regression, were performed. The multivariate linear regression with a gamma-link function was selected as the model with the best fit. The average annual PM 2.5 levels in Kampala and Jinja were 41.1 μg m −3 (±18.91 μg m −3 ) and 25.6 μg m −3 (±15.5 μg m −3 ), respectively, significantly exceeding the recommended World Health Organisation annual guideline values of 5 μg m −3 . Meteorological parameters exhibited varying degrees of relationships with PM 2.5 in both cities; multivariate regression indicated that meteorological factors could explain about 18% of the variation of PM 2.5 in Kampala and 7% in Jinja. Both cities experienced a decrease in PM 2.5 levels during the COVID-19 pandemic lockdown with Kampala experiencing a 31% reduction (average decrease of 11.2 μg m −3 ) and Jinja a 17% reduction (average decrease of 3.8 μg m −3 ). This study provides insights into the air quality challenges faced by a rapidly urbanising city in sub-Saharan Africa, the promise of locally made low-cost sensors, and how meteorology influences local air pollution and lays the foundation for informed decision-making to safeguard public health and promote a sustainable environment. The findings highlight the urgent need for targeted interventions and policy initiatives to address air pollution in Uganda.